Marketing Management in Sports - example of Dubrovnik sport clubs - Peručić, Doris; Joković, Maro (Oeconomica Jadertina, 2018)
Marketing plays a key role in society as a whole. Sports marketing encompasses all processes for creating and delivering value and transmitting its message, starting from the specific conditions in which relationships between market players are formed and how it affected the success of sport clubs and sporting events. In a large number of sports clubs, there is still no systematic application of marketing. The paper deals with the application of marketing in Dubrovnik sport clubs s been developed. The survey was conducted by a deep interview with leading people of the most successful Dubrovnik sport clubs and with the Secretary of the Dubrovnik Association of Sports. The causes of non-implementation of planning and systematic marketing application in the sports facilities in Dubrovnik, current marketing activity, problems encountered and the guidelines for a better understanding of the importance of marketing in sports were presented thereto. The research has confirmed that there is no systematic application of marketing in Dubrovnik sports facilities and that marketing activity activities are mostly reduced to numerous forms of marketing communication with the target market segments. Management awareness of the importance of sports marketing is developed, club leaders and Association point out the exigency to establish marketing departments within clubs, but in practice this has not yet been realized. Along with lack of financial resources, insufficient understanding of marketing as a business philosophy is one of the main reasons for not applying systematic marketing practices to sports facilities. To successfully manage marketing in sports facilities, it is crucial to engage sports marketing professionals/managers, but at the same time keep in mind that this is a club comprehensive initiative that drives its vision, mission, and strategic planning.